Study on Ni-(Ce, Zr, M)O2-δ Anode for Direct Internal Reforming SOFC Fueled by Biogas. (10th July 2019) - Takata, Shotaro; Sakamoto, Mio; Yamamoto, Takuya; Tamazaki, Fuminori; Shiratori, Yusuke
Abstract : 50 mol% ceria-50 mol% zirconia solid solution ((Ce0.5 Zr0.5 )O2-δ : CZ) with high oxygen storage capacity (OSC) has the significant effect on preventing carbon deposition during biogas reforming. Ni-CZ and Ni-CZY2.5 (2.5 mol% YO1.5 added) powder catalysts were prepared, and their catalytic activities for the dry reforming of methane (DRM) were evaluated. In the DRM tests, strong contribution of a reverse water-gas shift reaction was confirmed. Considerable suppression of coking confirmed after the DRM test with Ni-CZ indicates that lattice oxygen in CZ contributed to the removal of carbon formed on the catalyst surface. Coking could be further suppressed by increasing the mobility of O 2- by Y 3+ doping to introduce oxygen vacancies.